Sosialisasi Pentingnya Gizi Ikan Di Saka Bakti Husada Sungai Kelambu Kecamatan Tebas: Socialization of the Importance of Fish Nutrition in Saka Bakti Husada Sungai Kelambu Tebas District - Sakira Marantika; Anggi; Irfansyah; Erdika Epril Saputra; Iwan Saputra (Pakis Journal Institute, 2022)
One source of food that is rich in nutrients is found in fish. Fish has a fairly high source of protein. Protein in fish has a complete composition and amount of essential amino acids. Protein in fish is higher when compared to beef, chicken, and others. This activity aims to provide an understanding of the importance of nutrition and the benefits of eating fish in Saka Bakti Husada in Tebas District. The methods used in this activity are lectures and question and answer sessions. The results of this activity showed that members of saka bakti husada listened carefully to the material presented and asked questions about material that was not understood, resulting in a two-way interaction between the presenter and the audience. The active members of the Sungai Kelambu SBH show that members are interested in the material presented and the members' high curiosity even though there is a need for better improvements.